2021
DOI: 10.2147/ppa.s303279
|View full text |Cite
|
Sign up to set email alerts
|

Patient Preferences for Subcutaneous versus Intravenous Administration of Treatment for Chronic Immune System Disorders: A Systematic Review

Abstract: Background: For many chronic immune system disorders, the available treatments provide several options for route of administration. The objective of this systematic literature review is to inform discussions about therapy choices for individual patients by summarizing the available evidence regarding the preferences of patients with chronic immune system disorders for intravenous (IV) or subcutaneous (SC) administration. Methods: Searches of the MEDLINE, Embase and Cochrane Library databases were conducted usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 49 publications
(25 citation statements)
references
References 60 publications
(315 reference statements)
2
21
0
2
Order By: Relevance
“…Patients generally preferred 12 months duration of treatment benefit over 6 months but did not prefer the benefits to last 24 months, which may indicate patients' reluctance to commit to a therapy administered as an injection or oral pill beyond 1 year. The least preferred mode of administration was the monthly intravenous injection, which is aligned to the conclusions of a recent literature review in chronic immune system disorders that patients preferred treatment at home owing to the convenience and comfort of home treatment and the avoidance of having to attend hospital for an intravenous injection albeit less frequently administered [55]. Extensive subgroup analyses confirmed that observed differences in preferences were not explained by patient characteristics or disease history as participants' treatment preferences were generally consistent across subgroups.…”
Section: Discussionsupporting
confidence: 61%
“…Patients generally preferred 12 months duration of treatment benefit over 6 months but did not prefer the benefits to last 24 months, which may indicate patients' reluctance to commit to a therapy administered as an injection or oral pill beyond 1 year. The least preferred mode of administration was the monthly intravenous injection, which is aligned to the conclusions of a recent literature review in chronic immune system disorders that patients preferred treatment at home owing to the convenience and comfort of home treatment and the avoidance of having to attend hospital for an intravenous injection albeit less frequently administered [55]. Extensive subgroup analyses confirmed that observed differences in preferences were not explained by patient characteristics or disease history as participants' treatment preferences were generally consistent across subgroups.…”
Section: Discussionsupporting
confidence: 61%
“…Most UC patients are young of working age so infusion medications may be challenging and limit their quality of life. 46 Some patients are afraid of needles, hindering the use of subcutaneous drugs. 47 The use of oral drugs could reduce the indirect treatment costs as it could reduce hospital admissions and overcrowding by preventing the risks of viral infection in the current global pandemic context.…”
Section: Positioning Filgotinib In Ucmentioning
confidence: 99%
“…Of note, while many physicians think that patients prefer subcutaneous treatments over intravenous administration, this is not true for all patients ( 117 ). Some patients prefer IV administration with reasons given varying from less frequent dosing, convenience, the chance for interaction with hospital staff, and reassurance with medical presence ( 120 ).…”
Section: Important Considerations For the Physician In Case Of Non-re...mentioning
confidence: 99%